Reflection of Women Struggle Through the Main Character in Olivia Newman’s Where the Crawdads Sing (2022) - Thasyalina Amarthalia; Sudarisman, Yoga; Syarifudin, Bunyamin Faisal (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2025)
This study aims to analyze how Kya's character reflects the struggle of women in the context of feminism in Where the Crawdads Sing (2022). This is done to find out whether there are elements of feminism in Kya Clark's character in Where The Crawdads Sing (2022). The method used is qualitative research. In this study, researchers used feminist analysis to examine the characters in the movie and also examined transcripts integrated with Simone de Beauvoir's feminism. The main data source in this study is the character development of Kya from the main character in the movie Where The Crawdads Sing (2022). The data collection technique used is documentation in the movie Where The Crawdads Sing (2022) which highlights Kya's character that contains elements of feminism, interpreting the results of data collection and conclusions. The data analysis technique of this research uses feminist analysis by observing, identifying characters, and concluding. The results of this study state that Kya's character reflects the struggle of women in the context of feminism in the film Where The Crawdads Sing (2022) has five stages of how Kya reflects the struggle of women which include such as independence, freedom, social stigma, discrimination, harassment and oppression.